Concentration Dependence Orange Light Generation Through Sm3+-Doped Soda Lime Alumino Borate Glasses for Orange Laser Medium Material; Physica Status Solidi A; Vol. 222, iss. 12 - Jarucha N. Nawarut; Ruangtaweep Y. Yotsakit; Meejitpaisan P. Piyachat; Hong Joo Kim; Boontueng Ph. Phongnared; Kobda Ch. Chinorat; Ritjoho N. Narongrit; Sanghangthum T. Taweap; Valiev D. T. Damir Talgatovich; Kaewkhao J. Jakrapong (2025, 2025)
Title screen